Strengthening international ties: SWFU-UiTM inbound program 2025 a resounding success - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
Universiti Teknologi MARA (UiTM) Pahang Branch successfully hosted an Inbound Mobility Program in collaboration with Southwest Forestry University (SWFU), China, from 15 to 29 May 2025. The two-week program was almed at fostering academic exchange, cultural immersion, and research collaboration among students and staff from both institutions.